Mechanization outsourcing clusters and division of labor in Chinese agriculture - Zhang, Xiaobo; Yang, Jin; Reardon, Thomas (International Food Policy Research Institute, 2020)
Despite small landholdings, a high degree of land fragmentation, and rising labor costs, agricultural production in China has steadily increased. If one treats the farm household as the unit of analysis, it is difficult to explain the conundrum. When seeing agricultural production through the lens of the division of labor, the puzzle can be easily solved. In response to rising labor costs, farmers outsource some power-intensive stages of production, such as harvesting, to specialized mechanization service providers, which are often clustered in a few counties and travel throughout the country to provide harvesting services at competitive prices. Through such an arrangement, smallholder farmers can stay viable in agricultural production.